PUBLIC PERCEPTION REGARDING MONEY POLITICS IN GENERAL ELECTION 2019 (COMPARTIVE STUDY ON TEGAL CITY AND TEGAL REGENCY) - Sutjiatmi, Sri; Akta Padma Eldo, Dwian Hartomi; Zainudin, Arif (Department of Government, FISIP, Universitas Padjadjaran, 2020)
This paper is intended to look at the condition of Indonesia related to the still rampant occurrence of money politics which is a problem in the community when the 2019 elections simultaneously. This research takes a case study between Tegal City and Tegal Regency. The interesting thing in this study is to see how the community's assessment of the Tegal city and Tegal Regency groups regarding money politics in the 2019 elections simultaneously. The method used is a mixed method (between Mixed Methods) between quantitative and qualitative, by calculating the Solvin formula by deepening the analysis by interviewing the speakers directly. The results of the study showed that the people of Tegal City had a relatively high attitude of not paying attention to the Politics of Money in the General Election relating to the political money of the General Elections in 2019 at the same time. Unlike the people of Tegal Regency who consider money politics as a culture that is difficult to remove. Also interesting is the beginner voter group Tegal Regency has a fairly high knowledge about money politics that can damage the democratic system compared to the Beginner voters in Tegal City.gb777